In Search of Resistance Against Fusarium Ear Rot: Ferulic Acid Contents in Maize Pericarp Are Associated With Antifungal Activity and Inhibition of Fumonisin Production - Martínez-Fraca, Javier; de la Torre-Hernández, M. Eugenia; Meshoulam-Alamilla, Max; Plasencia, Javier (Frontiers in Plant Science, 2022)
Fusarium verticillioides is a fungal pathogen of maize that causes seedling blight, stem rot, and Fusarium ear rot. Fungal infestation of maize kernels and ears affects grain quality from the ensuing mycotoxin buildup. Among the mycotoxins produced by F. verticillioides, fumonisins accumulate to high levels in Fusarium-infected maize kernels, fumonisin B1 (FB1) being the most abundant in naturally infected maize. Achieving resistance to Fusarium ear rot has been challenging, as various environmental factors facilitate fungal infection. Among the maize grain components that contribute to resistance to F. verticillioides infection, the pericarp is the first barrier faced by the fungus and thus plays a key role. Phenolic acids are major constituents of maize pericarp, of which ferulic acid (FA) is the predominant molecular species. In this work, we explored the relationship between FA levels, fungal infection, and FB1 production in 51 maize genotypes and whether the antioxidant activity of FA might play a role. We confirmed that FA is a major component of the seed pericarp, whose levels as bound FA varied between 4.5 to 26.3 mg/g across maize genotypes. We selected two pools of five maize varieties, with contrasting FA contents: low FA (LFA; 6.14 ± 0.40 mg/g) and high FA (HFA; 15.49 ± 1.31 mg/g). In vitro, HFA extracts were more potent in inhibiting fungal growth than LFA extracts, with effects comparable to FA concentrations in the 0.25 - 0.50 mM range. We also established a kernel assay to study F. verticillioides colonization and FB1 production in the LFA and HFA genotypes. Fungal colonization was significantly lower in HFA genotypes relative to LFA genotypes, based on ergosterol levels. Moreover, FB1 production was also inhibited in the HFA genotypes. Importantly, the antioxidant activity of maize pericarp extracts was associated with FA contents, with HFA extracts exhibiting a greater antioxidant activity than LFA extracts. Overall, our results highlight the role of FA and its antioxidant activity on resistance to Fusarium ear rot and provide the basis of a phenotypic trait that can be deployed for breeding selection.